2019
DOI: 10.1016/j.seppur.2018.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Study of the degradation of an organophosphorus pesticide using electrogenerated hydroxyl radicals or heat-activated persulfate

Abstract: The use of pesticides and their release into the natural environment constitutes a direct threat for the environment and the living beings especially the human health. Consequently, the development of technics to detoxify the pesticide residues to reduce at least areas and contaminated matrix is needed. In the present work, a comparative study was performed on the chemical oxidation of an organophosphorus compound, the dimethoate (DIM), with sulfate radicals and hydroxyl radicals. Both oxidants are generated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…Usually, the higher the temperature, the higher is the radical generation rate and, therefore, the faster is the pollutant's removal [64]. This correlation fits properly to the Arrhenius equation (Equation (8)) [65,66]. Moreover, the contaminant removal rate adjusts in most of the studied cases to pseudo-first order kinetics (Equation (9)) [65][66][67].…”
Section: Thermal Activationsupporting
confidence: 65%
See 1 more Smart Citation
“…Usually, the higher the temperature, the higher is the radical generation rate and, therefore, the faster is the pollutant's removal [64]. This correlation fits properly to the Arrhenius equation (Equation (8)) [65,66]. Moreover, the contaminant removal rate adjusts in most of the studied cases to pseudo-first order kinetics (Equation (9)) [65][66][67].…”
Section: Thermal Activationsupporting
confidence: 65%
“…This correlation fits properly to the Arrhenius equation (Equation (8)) [65,66]. Moreover, the contaminant removal rate adjusts in most of the studied cases to pseudo-first order kinetics (Equation (9)) [65][66][67]. However, extremely high temperature does not achieve better micropollutant degradation because those conditions may lead to radical-radical reactions instead of radical-contaminant reactions due to the high radical's concentration [63,64].…”
Section: Thermal Activationsupporting
confidence: 51%
“…The influence of various process variables on the degradation of a myriad of organic compounds has been described in some literature sources. For example, some authors [13,14] identified the PS concentration to be a major influential factor, which is positively correlated with the pollutant degradation efficiency. The pH dependence was studied and was attributed to a difference in relative abundancy of the radicals present in the reaction mixture [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Discharge of toxic effluents generated from pesticide manufacturing industries into water bodies has become one of the major concerns in environmental safety. Therefore, various physical and chemical treatment methods implemented for the remediation of OP contaminated water include wet oxidation, electrochemical oxidation (Aimer et al, 2017;Aimer et al, 2019), photocatalytic oxidation (Petsas and Vagi, 2018), fumigation (Sintuya et al, 2018), etc.…”
Section: Introductionmentioning
confidence: 99%